Exploitation of bird resources among prehistoric sea-nomad societies of the Beagle Channel region, southern South America - Tivoli, Angelica Montserrat (2010)
The relationship between birds and prehistoric hunter-gatherer-fishers of the Beagle Channel region is analyzed here. In this sense, the main goal of this paper is to characterize the utilization of birds by these sea-nomad societies, and to explore changes and continuities of that relationship in early and recent periods of the regional sequence. Data from eleven zooarchaeological assemblages divided in two periods is included in the analysis for comparative purposes. Results show that the late period (circa 1500-100 years BP) was characterized by an important increase in birds exploitation in comparison to early times (circa 6000 years BP), and by changes in taxa selection. Consequently, these trends suggest changes in bird use patterns of for later moments, mostly characterized by massive captures of birds with high relative return rate (vg cormorants), and captures of taxa that usually have pelagic habits.